2021
DOI: 10.46542/pe.2020.202.149159
|View full text |Cite
|
Sign up to set email alerts
|

Determining the best practices for remote experiential rotations

Abstract: Introduction: During the COVID-19 pandemic, clinical sites have closed their doors to student placements, leading to the implementation of remote rotations. The purpose was to determine best practices for distance preceptorship from the student’s perspective. Methods: A survey was sent to the pharmacy students at the Leslie Dan Faculty of Pharmacy who have completed at least one remote rotation. Results: Forty-eight out of 121 students (39%) completed the survey. It was found that 83% of the students were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hundal and colleagues (2021) invited students to virtual orientations, conducted daily check-ins and connected with students to gain feedback on progress and concerns during the rotation to develop student engagement and motivation. From a student's perspective, Zhu & Brown (2021) demonstrated that students stayed motivated during rotations when they built a positive rapport with preceptors, and therefore, resources should be created to enable preceptors to achieve this.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hundal and colleagues (2021) invited students to virtual orientations, conducted daily check-ins and connected with students to gain feedback on progress and concerns during the rotation to develop student engagement and motivation. From a student's perspective, Zhu & Brown (2021) demonstrated that students stayed motivated during rotations when they built a positive rapport with preceptors, and therefore, resources should be created to enable preceptors to achieve this.…”
Section: Resultsmentioning
confidence: 99%
“…The authors adapted a survey that explored best practices in remote rotations from pharmacy students' perspectives (Zhu & Brown, 2021). Informed by a literature review of remote learning and precepting in the health disciplines, the authors focused the questions to include aspects relevant to precepting remote rotations, including preceptor preparation (Ho et al, 2021), the preceptor/student relationship (Rand & Pajarillo, 2015), access to technology (Johnson, 2019), preceptor satisfaction and professional development needs (Ackman & Romanick, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key factors in a remote rotation were setting expectations, good communication, getting to know the preceptor, and having a distraction-free work environment. These previously mentioned factors could become corrective actions to maximize the learning objectives of the internship program (Almetwazi et al, 2020;Zhu and Brown, 2020).…”
Section: Slack Time For Mentoring In Pandemic Conditionsmentioning
confidence: 99%
“… 2 , 3 , 4 Shifts in pharmacy experiential education were documented over the course of the pandemic as pharmacy learners and practice educators learned to navigate virtual experiential education. 5 , 6 , 7 Currently, there is limited literature on developing best teaching practices that are conducive to students’ success in a virtual environment.…”
Section: Introductionmentioning
confidence: 99%